Direct bioconversion of domestic wastewater sludge as a new substrate for bioethanol production through optimization of media - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Razak, A A (2006)
A lab-scale study was conducted to produce bioethanol using wastewater sludge as substrate by the yeast Saccharomyces cerevisiae. Direct bioconversion process was applied through media optimization for bioethanol production. The statistical optimization was carried out with four different media compositions such as the concentration of sludge, co-substrate of wheat flour, ammonium nitrate (NH4NO3) and potassium dihydrogen phosphate (KH2PO4) with five levels by central composite design. A polynomial regression model equation was developed by using experimental values obtained from experimental design. The model predicted the optimum media compositions which were 1.5% (v/v) of sludge, 3% (v/v) of co-substrate, 500 mg/L of NH4NO3 and 400 mg/L of KH2PO4. The bioethanol yield was obtained with 4.6% under these conditions. The coefficient of determination (R2) for the model is 96% indicating that the bioethanol production is very highly associated with the independent variables (media compostion).